ViewpointExploring leadership through literature - an audacious experiment. Issue 4 (10th November 2021) - Deal, Terrence E.; Lieberman, Devorah; Meek, Jack Wayne
Abstract : Purpose: The purpose of the paper is to address the following question: What can novels reveal about what leadership nonfiction sources miss or obscure? Design/methodology/approach: The paper reviews the benefits that are derived from the use of literature in the examination of leadership, compares and contrasts three novel experiments in the examination of literature and leadership, and examines the impact of one approach as reflected in student assignments and exit interviews. Findings: Student reflection papers morphed from descriptive reviews to reflections expressed through poetry, artwork and personal experiences. Students also deepened their views on what leadership is and means. Exit interviews revealed student significant reflection on personal views in a number of areas. The longitudinal follow up of students expanded their flexibility and ability to listen and understand how and why people approach leadership in different ways. They also felt it increased their openness to new or different approaches and encouraged them to think more independently. Practical implications: One implication of the approach of this class is how the authors embraced questions to guide the students and faculty. Instead of listing topics and assigning categorical meaning, the approach of the class was organized around questions, such as, "is leadership real or imagined? Am I ready to take responsibility? Social implications: The power of storytelling is unmistakable. The value of storytelling is that it allows the reader to escape from the day-to-day challenges we face to find how others are facing challenges sometimes very similar to our own. Originality/value: The article compares and contracts three experiments in the examination of literature and leadership. The paper then examines one approach to literature and leadership in terms of the impact on students (papers, exit interview and longitudinal follow-up). Findings are assessed with the works of Gardner, Bennis and Hartley stressing the possibilities of storytelling as a unique approach to studying and practicing leadership.